PARENTAL ENGAGEMENT ON CHILDREN CHARACTER EDUCATION: THE INFLUENCES OF POSITIVE PARENTING AND AGREEABLENESS MEDIATED BY RELIGIOSITY - Raden Rachmy Diana; Muhammad Chirzin; Khoiruddin Bashori; Fitriah M Suud; Nadea Zulfa Khairunnisa (Jurnal Cakrawala Pendidikan, 2021)
Parents have an important role in introducing character education to children. Positive parenting and agreeableness are considered to have essential influences on parent engagement in children’s character education mediated by religiosity. This study aimed to examine the effects of positive parenting and agreeableness towards parental engagement in character education with religiosity as the mediator. Data were obtained using five instruments, namely the parental engagement scale, agreeableness scale, religiosity scale, Islamic knowledge test items, and the positive parenting scale. The population of this research was the parents of students of Muhammadiyah elementary schools located in the Special Region of Yogyakarta, Indonesia. By cluster random sampling technique, the study involved 210 parents. The collected data were analyzed using the SEM technique. The results of this study show that: (1) there was a significant relationship between positive parenting and agreeableness on parental engagement, (2) religiosity worked as a mediator of the relationship between positive parenting and agreeableness in parental engagement, and (3) religiosity worked better as the mediator of agreeableness than positive engagement. It was concluded that the correlation between agreeableness and parental engagement would not be formed without religiosity as a mediator.